Equilibrium Positive Interest Rates: A Unified View - Jin, Yan; Glasserman, Paul (Review of Financial Studies, 2001)
This article develops precise connections among two general approaches to building interest rate models: a general equilibrium approach using a pricing kernel and the Heath, Jarrow, and Morton framework based on specifying forward rate volatilities and the market price of risk. The connections exploit the observation that a pricing kernel is uniquely determined by its drift. Through these connections we provide, for any arbitrage-free term structure model, a representative-consumer real production economy supporting that term structure model in equilibrium. We put particular emphasis on models in which interest rates remain positive. By modeling the dynamics of the drift of the pricing kernel, we construct a new family of Markovian-positive interest rate models.